Corporate codes of conduct: Are three generations sufficient to ensure the effective enforcement of labour rights? - Aneta Tyc (Bratislava Law Review, 2018)
In the 1970s, the number of reports concerning unethical or illegal activities of multinational corporations increased and led to discussions within international organisations. In 1976, the OECD was first to adopt its Guidelines for Multinational Enterprises. The ILO adopted its Tripartite Declaration of Principles concerning Multinational Enterprises and Social Policy in 1977, and UN issued the Global Compact in 2000. Subsequently, many codes of conduct have been established to provide a stable framework in which MNEs conduct their business. The purpose of this paper is to assess, through the prism of three generations of codes, if self-regulation is sufficient to ensure the effective enforcement of labour rights. I fill the gap in existing research by providing a comprehensive explanation for the shortcomings of this instrument. Research indicates that there is a lack of involvement of social partners in the decision-making process leading to the adoption of codes of conduct. Once adopted, they impose lower standards than the public regulatory frameworks. They are more selective in their choice of labour rights. There are also many difficulties in implementing, monitoring and enforcing a corporate code of conduct. These tools mainly address marketing aims and respond to the unfavourable publicity produced by the media about the inconsistency of certain corporate policies with international labour standards. I conclude by discussing how codes of conduct could be transformed to more eectively address workers’ rights.